Low-cost table-top experiments for teaching multi-scale geophysical fluid dynamics - Moscoso, Jordyn E.; Tripoli, Rachel E.; Chen, Shizhe; Church, William J.; Gonzalez, Henry; Hill, Spencer A.; Khoo, Norris; Lonner, Taylor L.; Aurnou, Jonathan M. (Frontiers in Marine Science, 2023)
Multi-scale instabilities are ubiquitous in atmospheric and oceanic flows and are essential topics in teaching geophysical fluid dynamics. Yet these topics are often difficult to teach and counter-intuitive to new learners. In this paper, we introduce our state-of-the-art Do-It-Yourself Dynamics (DIYnamics) LEGO robotics kit that allows users to create table-top models of geophysical flows.Deep ocean convection processes are simulated via three experiments – upright convection, thermal wind flows, and baroclinic instability – in order to demonstrate the robust multi-scale modeling capabilities of our kit. Detailed recipes are provided to allow users to reproduce these experiments. Further, dye-visualization measurements show that the table-top experimental results adequately agree with theory. In sum, our DIYnamics setup provides students and educators with an accessible table-top framework by which to model the multi-scale behaviors, inherent in canonical geophysical flows, such as deep ocean convection.